Development of a clear-sky model to determine circumsolar irradiance using widely available solar radiation data - Abreu, Edgar (2020)
Accurate assessment of the solar irradiance reaching the absorber of concentrating solar power (CSP) systems is crucial for accurate energy generation estimates as well as for power plants design and operation. Due to a larger aperture angle, direct normal irradiance (DNI) measurements taken by pyrheliometers include circumsolar normal irradiance (CSNI), i.e., the diffuse radiance from the vicinity of the sun disk, which in some cases is not totally captured by the CSP systems because of their lower aperture angles. This work reports the modelling of DNI and CSNI using a radiative transfer model and atmospheric measurements and aims to develop a fast and simple model to estimate the CSNI based on more common solar irradiance measurements such as the DNI, global horizontal irradiance (GHI) and diffuse horizontal irradiance (DHI). The proposed model performs better than other models available in the literature for the six locations analysed (scattered around the globe), thus contributing to a more accurate solar resource assessment and CSP systems design and operation.